2018
DOI: 10.1039/c7nr08388b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-deficient photostable Cu2O for enhanced visible light photocatalytic activity

Abstract: Oxygen vacancies in inorganic semiconductors play an important role in reducing electron-hole recombination, which may have important implications in photocatalysis. Cuprous oxide (Cu2O), a visible light active p-type semiconductor, is a promising photocatalyst. However, the synthesis of photostable Cu2O enriched with oxygen defects remains a challenge. We report a simple method for the gram-scale synthesis of highly photostable Cu2O nanoparticles by the hydrolysis of a Cu(i)-triethylamine [Cu(i)-TEA] complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 53 publications
(56 reference statements)
2
60
0
Order By: Relevance
“…Band energies were investigated by valence band XPS (Figure S4a–c); the VB potential maxima of hierarchical Cu 2 O and the Cu 2 O/rGO nanocomposite were +1.30 and +1.10 eV respectively relative to the Fermi level, and corresponding CB minima edges (derived from the optical band gap and valence band XP spectra) were −1.12 eV and −1.03 eV for Cu 2 O/rGO. The CB minimum is therefore unaffected by formation of the Cu 2 O/rGO heterojunction, albeit more negative than previous reports (e. g. −0.42 for oxygen‐deficient Cu 2 O nanoparticles), and in both cases much greater than required for photocatalytic hydrogen production from water (−0.65 eV at pH )…”
Section: Resultsmentioning
confidence: 52%
“…Band energies were investigated by valence band XPS (Figure S4a–c); the VB potential maxima of hierarchical Cu 2 O and the Cu 2 O/rGO nanocomposite were +1.30 and +1.10 eV respectively relative to the Fermi level, and corresponding CB minima edges (derived from the optical band gap and valence band XP spectra) were −1.12 eV and −1.03 eV for Cu 2 O/rGO. The CB minimum is therefore unaffected by formation of the Cu 2 O/rGO heterojunction, albeit more negative than previous reports (e. g. −0.42 for oxygen‐deficient Cu 2 O nanoparticles), and in both cases much greater than required for photocatalytic hydrogen production from water (−0.65 eV at pH )…”
Section: Resultsmentioning
confidence: 52%
“…However, compared with bare ZnO, all BiNPs/ZnO composites exhibited stronger adsorption intensity in the visible light region. At the same time, the band gap energy estimated from the intercepts of the tangents to the plots of (Ahν) 2 vs. photon energy was shown in Figure 5b [42,43], which also suggested that the band gap energy of the Bi-ZnO-80 composite was not significantly changed, as compared with that of pure ZnO. Therefore, the enhancement of absorption in the visible light region of BiNPs/ZnO was not due to the change of the band gap energy.…”
Section: Introductionmentioning
confidence: 88%
“…EnormalCnormalB and EnormalVnormalB are edge potential of conduction and valence band respectively.normalEnormalg is the bandgap of the semiconductor, Ee is the free electron energy on the hydrogen scale (4.5 eV) and χ is absolute electronegativity of the semiconductor. The value of χ for MoS 2 and Cu 2 O is 5.32 and 5.305 respectively …”
Section: Resultsmentioning
confidence: 99%
“…The absorption peak of MB at 664 nm, in Figure (a) also, show blue‐shift and decrease in absorption intensity (hypsochromic effect). This process corresponds to the de‐methylation of MB dye with various intermediate structures . Therefore, the ternary composite MoS 2 /rGO/Cu 2 O structure with its lowest recombination rate and separation efficiency of photogenerated charge carriers are responsible for the degradation phenomenon.…”
Section: Resultsmentioning
confidence: 99%